Pairwise test suite generator tool based on harmony search algorithm (HS-PTSGT) - Lai, Yi Xiang (2014)
In the era of technology, software systems are around us in our daily life. Thus, a good system is needed to ensure the well function of gadget and devices with software embedded. However, exhaustive testing that required lot of time and financial resources is normally impossible. This thesis is about the research on developing a pairwise test suite generator tool based on Harmony Search Algorithm (HS-PTSGT) to generate optimum test suite. Test suite which considers all interaction of at most two factors will be generated from two-valued input parameters that are not more than 500. Users are allowed to enter parameter and values through the graphical user interface, and test cases will be generated through the execution of Harmony Search Algorithm involved random initialization of harmony memory and harmony memory improvisation. From the comparison with other existing pairwise testing tools in term of size, it is shown that the strategy used in HS PTSGT can effectively generate optimum test suite with minimized test data and performed better on certain parameter size.